2018
DOI: 10.3389/fmicb.2018.01488
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection Increased Anti-dsDNA and Enhanced Lupus Severity in Symptomatic FcγRIIb-Deficient Lupus Mice

Abstract: The defect on Fc gamma receptor IIb (FcγRIIb), the only inhibitory FcγR, has been identified as one of the genetic factors increasing susceptibility to lupus. The prevalence of Helicobacter pylori (HP) and FcγRIIb dysfunction-polymorphisms are high among Asians, and their co-existence is possible. Unfortunately, the influence of HP against lupus progression in patients with lupus is still controversial. In this study, the interactions between these conditions were tested with HP infection in 24-week-old FcγRII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Yamanishi et al have demonstrated B-1-cell activation using HP urease, leading to the creation of anti-ssDNA antibodies (16). In a recent animal study, Surawut et al found that HP infection increased anti-dsDNA and lupus severity in the symptomatic FcγRIIb-deficient lupus mouse model (23). Few clinical studies have been conducted to understand the correlation between HP infection and SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Yamanishi et al have demonstrated B-1-cell activation using HP urease, leading to the creation of anti-ssDNA antibodies (16). In a recent animal study, Surawut et al found that HP infection increased anti-dsDNA and lupus severity in the symptomatic FcγRIIb-deficient lupus mouse model (23). Few clinical studies have been conducted to understand the correlation between HP infection and SLE.…”
Section: Discussionmentioning
confidence: 99%
“…In FcγRIIb−/− mice, a polymorphism associated with SLE development, H. pylori infection was associated with increased SLE severity, higher levels of anti- H. pylori and anti-dsDNA antibodies, and increased production of splenic autoimmune cells compared with wild-type mice [ 53 ]. Urease induced the production of anti-ssDNA antibodies in animal models [ 31 ].…”
Section: Helicobacter Pylori and Systemic Lupus Erythematosusmentioning
confidence: 99%
“…11-13) despite the similar level of LPS and BG in blood (Fig. 4D,E) emphasizing the hyper-immune responses due to the inhibitory-signaling defect of FcGRIIb−/− group 3,23 . However, proteinuria, histopathology score and immunoglobulin deposition in glomeruli were not different between FcGRIIb−/− and pristane mice ( Figs.…”
Section: Gastrointestinal Leakage Enhanced Lupus Disease-severity In mentioning
confidence: 82%
“…Spleen apoptosis was detected by immunohistochemistry with anti-active caspase 3 antibody (Cell Signaling Technology, Beverly, MA, USA) (expressed as positive cells per high-power field) 22 and flow cytometry. The fluorochrome-conjugated antibodies against different molecules were used including; i) apoptosis indicators, annexin V and propidium iodide (PI), ii) B220 (B cell) and iii) F4/80 (macrophage) (BioLegend, San Diego, CA, USA) with FlowJo software 23 . www.nature.com/scientificreports www.nature.com/scientificreports/ Mesenteric lymph node analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation